El impacto de la crisis del capital y de la pandemia de COVID-19 en el Estado social español* - Mustafa, Patrícia Soraya [UNESP] (Cortez Editora Ltda, 2024)
This article presents part of a study conducted on the Spanish social State during the capital crisis that began in 2008 and later during the COVID-19 pandemic. The objective has been to understand the measures adopted in each of these historical periods and their impacts on the Social State. Below, some of the results obtained from a bibliographic, empirical and documentary research are presented.

Este artículo examina una parte de un estudio realizado en España sobre el Estado Social español durante la crisis del capital iniciada en 2008 y posteriormente durante la pandemia de COVID-19. El propósito ha sido entender las medidas adoptadas en cada uno de estos períodos históricos y sus impactos en el Estado Social. A continuación, se presentan algunos de los resultados obtenidos a partir de una investigación bibliográfica, empírica y documental.
The impact of the capital crisis and the COVID-19 pandemic on the Spanish social State**
Keywords: Spanish Social State; Capital crisis of 2008; COVID-19